Trauma at night from the perspective of the Mobile Emergency Care Service in Espírito Santo: an epidemiological analysis (Brazilian Journal of Health Research, 2023)
Introduction: Trauma is considered a major public health problem worldwide, due to deaths, sequelae and its overwhelming socioeconomic consequences. Objectives: To analyze the traumatic occurrences and factors associated with trauma at night that occurred with victims assisted by the Mobile Emergency Care Service of Espírito Santo, in the years 2020 and 2021. Methods: Cross-sectional observational study of 23,445 trauma occurrences, divided into two groups: daytime trauma and nighttime trauma. The variables on the social, demographic and clinical profile were collected from data from the Emergency Medical Regulation System, and analyzed univariately and multivariately. Results: 64.2% of the traumas occurred during the day, while 35.8% occurred during the night. The factors associated with the occurrence of nocturnal trauma were: male gender, age group 25 – 34 years, weekend, home origin, Serra Region, non-critical victims, referral from the Advanced Support Unit, aggression, bladed weapon, fall from own height, falling from a moving vehicle, death on the scene and transporting victims to public hospitals. Conclusion: The profile of trauma victims assisted by the Mobile Emergency Care Service in Espírito Santo corresponds to that found in Brazil, however, it differs according to the day and night periods. It is expected to improve public health policies aimed at trauma prevention and the integration of Trauma Network components.
Keywords: Wound and injuries; Emergency Medical Services; Health profile